Starch digestibility properties of bread from hard red spring wheat cultivars released in the last 100 years. Issue 1 (9th October 2019) - Simsek, Senay; Budak, Bilge; Schwebach, Catherine Suzanne; Ovando‐Martínez, Maribel
Abstract: Background and objectives: There have been concerns that there is a link between the carbohydrate properties of modern wheat cultivars and increasing levels of obesity and diabetes worldwide. This research was conducted to determine starch composition and digestibility of thirty historic and modern hard red spring wheat cultivars and to evaluate whether there were statistical differences between the genotypes in relationship to the release year. Findings: There were no significant differences ( p  < .05) between historic and modern wheat cultivars for amylose content in flour or for amylose and amylopectin molecular weight in flour and bread samples. Starch digestibility in bread did not show significant differences ( p  < .05) among cultivars, and there was no significant correlation ( p  < .05) with the release year and the SDS, HI, and eGI. Conclusions: Starch digestibility of bread prepared from historic and modern wheat cultivars is not related to release year. It is unlikely that wheat breeding practices have caused wheat to be more rapidly digestible and the digestibility could be more related with the bread‐making process or formula than the release year. Significance and novelty: Knowledge about the effect of the release year on starch in historical and modern wheat cultivars helps us to support that wheat breeding is not related to increased incidence of chronic disease.